Analisis Peningkatan Kualitas pada Rantai Pasok Buah Pepaya Calina (Jurnal Manajemen dan Organisasi, 2016)
Due to the fact that post-harvest handling of local fruits especially in Calina papaya supply chain (IPB 9) has experience problems that can affect the value of its quality appearance, quality improvement is absolutely required. The purposes of this research are 1) Identifying the key attributes of Calina papaya quality improvement based on desires of consumers and to know the level of customer satisfaction using Quality Function Deployment (QFD); 2) Analyzing the causes of Calina papaya quality problems, and 3) Analyzing strategies or ways to improve the quality of Calina papaya in Indonesia. The results of this research show that there are three main attributes of customer satisfaction; namely, the sweet taste, color of fruit meat, and texture of fruit meat. Supply chain activities that have the highest interests of rate based on analysis of QFD are the maintenance (value 521) of cultivation. There are two attributes that have mismatches of quality; bruise and pests-diseases, caused by the raw materials, management, labor, environment, machine and method. The highest priority that can be chosen as the alternative strategy is increasing production capacity, product quality, and food safety assurance by expanding the distribution network. Keywords : Calina papaya, quality function deployment, strategy, quality